Application of Probiotics for Organic Matter and Enhancement of Growth Performance in White Shrimp (Litopenaeus vannamei) - Muhammed Jefri; Woro Hastuti Satyantini; Adriana Monica Sahidu; Daruti Dinda Nindarwi; Rozi Rozi (Jurnal Ilmiah Perikanan dan Kelautan)
Highlights • Litopenaeus vannamei has been established as alternative to Penaeus monodon to shrimp farming in several countries. • Increased importance of in situ microorganisms both in regulating biogeochemical cycles within the culture environment and in directly affecting shrimp growth and survival. • To improve water quality in aquaculture is the application of probiotics and/or enzymes to ponds.